Persepsi Pedagang Bahan Pokok Terhadap Penggunaan QRIS di Pasar Tradisional Pucang Anom Surabaya - Anggraini, Fitri; Laily, Dona Wahyuning; Khomah, Isti (Universitas Galuh, 2025)
Advancing technology has enabled the creation of safer and more efficient payment systems, such as mobile application payments via QRIS (Quick Response Code Indonesian Standard). QRIS usage is not only applied in modern markets but has also been implemented in traditional markets. With the adoption of QRIS across various sectors, including traditional markets, it is expected to bring significant changes to transaction patterns that are typically cash-based. Despite its implementation, not all traders in traditional markets adopt QRIS technology due to limited knowledge and understanding of the technology and concerns about the security of digital payments. Therefore, the objective of this study is to analyze traders' perceptions of QRIS usage in traditional markets. This study will involve a sample of 75 respondents who are staple goods traders in Pucang Anom traditional market in Surabaya. The factors to be examined include ease of use, perceived benefits, credibility, and frequency of use. The results will be analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS) method. By analyzing these factors, this study aims to provide a deeper understanding of the interest in using QRIS among staple goods traders in Pucang Anom traditional market. It is also hoped that this research will offer insights for policy development and more effective educational strategies to encourage QRIS adoption among traders in traditional markets, especially in the Pucang Anom area of Surabaya.